2018
DOI: 10.1044/2017_lshss-16-0081
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Scoring and Classification Accuracy of Vocabulary Testing in Bilingual Children

Abstract: Downloaded From: http://lshss.pubs.asha.org/ by a ReadCube User on 01/10/2018 Terms of Use: http://pubs.asha.org/ss/rights_and_permissions.aspx specificity, however, we have no reason to expect high classification accuracy, even if conceptual scoring is used. Thus, we explore the diagnostic accuracy of conceptual vocabulary scoring to determine if using conceptual scoring with single-word vocabulary tests increased their sensitivity so they might contribute to the identification of SLI in bilingual children. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 76 publications
1
27
0
5
Order By: Relevance
“…For example, in a recent study, 247 English-Spanish bilingual children aged5-11 years, with DLD (BiDLD) or with typical language development (BiTLD) were compared on a naming task in both languages (Anaya et al 2018). The results revealed that BiDLD performed lower than BiTLD in naming accuracy, especially when responses from both languages were considered.…”
Section: Lexical Effects Of Dld In Bilingual Childrenmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, in a recent study, 247 English-Spanish bilingual children aged5-11 years, with DLD (BiDLD) or with typical language development (BiTLD) were compared on a naming task in both languages (Anaya et al 2018). The results revealed that BiDLD performed lower than BiTLD in naming accuracy, especially when responses from both languages were considered.…”
Section: Lexical Effects Of Dld In Bilingual Childrenmentioning
confidence: 99%
“…The effect of DLD within the population of bilingual children has been examined in the lexical domain using various measures, including naming (Anaya et al 2018, Kambanaros et al 2015, Khoury Aouad Saliby et al 2017, word associations (Holmström et al 2016) and lexical diversity measures in narrative production (Altman et al 2016). Across these production tasks, the trigger for target selection among the meaning-related alternatives differ (Gollan et al 2011).…”
Section: Lexical Effects Of Dld In Bilingual Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…We included these children because they had not been identified by their schools as presenting a low nonverbal IQ, and the children's PTONI scores did not correlate with their rates of zero-marked infinitival TO (r ≤ .13). Also, although many studies of SLI use a −1 SD cut score for nonverbal IQ, some use a −1.3, −1.5, or −2.0 SD cut score (e.g., Anaya, Peña, & Bedore, 2017;Desmottes, Meulemans, Patinec, & Maillart, 2017;Kapa, Plante, & Doubleday, 2017;Montgomery, Gillam, Evans, & Sergeev, 2017;Sanjeevan & Mainela-Arnold, 2017;Van Horne, Fey, & Curran, 2017). Finally, the practice of cognitive referencing to select children for studies of SLI has been discussed and questioned in various publications (see Ebbles, 2014;Leonard, 2014;Rice, 2016).…”
Section: Dialect Classificationmentioning
confidence: 99%